Cognitive activation in L1 literature classes: A content-specific framework for the description of teaching quality - Winkler, Iris (L1-Educational Studies in Language and Literature, 2020)
In recent years, the scientific determination of teaching quality has become a central topic and productive field within empirical classroom research. With respect to L1 literature education, there is no framework within which attempts can be made to consistently interpret domain-specific criteria of teaching quality. Against this background, this paper follows two main questions: What does teaching quality in L1 literature classrooms mean? How can teaching quality be operationalised? This paper argues that the construct of cognitive activation offers a suitable approach to integrate existing specifications of teaching quality in L1 literature classrooms and to identify and define characteristics of a content-specific view. The key result presented in this paper is a highly inferential coding system that operationalises cognitive activation for L1 literature classes. The operationalisation regards tasks in process to be indicators for cognitive activation. The theoretical conceptualisation is based on empirical data from a pilot study for the research project KoALa (Cognitive Activation through Tasks in Literature Classes). In this pilot study, six literature lessons were videotaped, involving analysis of the same short story with six different teachers and classes (107 students, grade 8, German “Gymnasium”).